Vocabulary: Common or Basic? - Kornai, András (Frontiers in Psychology, 2021)
Neither linguistics nor psychology offers a single, unified notion of simplicity, and therefore the simplest ‘core’ layer of vocabulary is hard to define in theory and hard to pinpoint in practice (Borin, 2012). In this paper we briefly survey the main approaches, and distinguish two that are highly relevant to lexicography: we will call these `common' and `basic'. We compare these approaches, and we point the reader at Kolmogorov complexity, unfamiliar as it may be to most working psychologists, lexicographers, and educators, as the best formal means to deal with core vocabulary.